2003
DOI: 10.1093/humrep/deg354
|View full text |Cite
|
Sign up to set email alerts
|

Heparan sulphate: a putative decondensing agent for human spermatozoa in vivo

Abstract: Our results indicate that heparin's decondensing ability in vitro is related to sulphation characteristics of the molecule and suggest that heparan sulphate, a structural analogue of heparin, could be a sperm-decondensing agent in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
50
1
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(58 citation statements)
references
References 30 publications
5
50
1
2
Order By: Relevance
“…In human ICSI, it has been shown that the sperm DNA damage is detrimental to fertility and has been regarded as a major factor in lowering embryo quality (Tomsu et al 2002, Virant-Klun et al 2002, blastulation rate (Seli et al 2004), and overall pregnancy rate after IVF (Evenson et al 2002, Bungum et al 2004, Henkel et al 2004, Virro et al 2004. Heparin was also used to induce nuclear decondensation (Vendrell et al 1998, Delgado et al 2001, Romanato et al 2003. The glycoprotein heparin receptors are present on human sperm plasma membrane (Delgado et al 1982).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In human ICSI, it has been shown that the sperm DNA damage is detrimental to fertility and has been regarded as a major factor in lowering embryo quality (Tomsu et al 2002, Virant-Klun et al 2002, blastulation rate (Seli et al 2004), and overall pregnancy rate after IVF (Evenson et al 2002, Bungum et al 2004, Henkel et al 2004, Virro et al 2004. Heparin was also used to induce nuclear decondensation (Vendrell et al 1998, Delgado et al 2001, Romanato et al 2003. The glycoprotein heparin receptors are present on human sperm plasma membrane (Delgado et al 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Binding of heparin to its receptors destabilizes sperm plasma membrane that in turn facilitates the incorporation of other molecules such as GSH into sperm nucleus (Marina et al 2003). Furthermore, the strong binding affinity of heparin for protamines can assist the formation of a highly insoluble complex that may promote sperm chromatin decondensation (reviewed in Romanato et al 2003). Combination of heparin and DTT may help to induce swelling of sperm nuclear matrix (Jager et al 1990).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure of sperm nuclear swelling using heparin and DTT mimics decondensation after fertilization, because both chemicals are analogs of components present in oocyte cytoplasm: disulfide-reducing glutathione (Sutovsky and Schatten, 1997) and heparan sulphate (Romanato et al, 2003). Care was taken to maintain the 3D structure of the nuclei using DNA-protein crosslinking by mild formaldehyde fixation.…”
Section: Discussionmentioning
confidence: 99%
“…The oocyte factors, known as sperm decondensation factors (SDFs), have been shown to induce this process (Moor & Gandolfi 1987, Miyara et al 2003. Several SDFs in oocytes that facilitate protamine removal, chromatin decondensation, and histone replacement have been identified to date (Romanato et al 2003, 2005, 2008, Inoue et al 2011, Julianelli et al 2012, Yadav et al 2013. It is suggested that SDFs are induced after GV breakdown in most mammals (Dozortsev et al 1995), but their roles and mechanisms of action in the oocyte cytoplasm are obscure at present.…”
Section: Discussionmentioning
confidence: 99%